2023
DOI: 10.1161/circulationaha.122.063014
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-33 Mediates Cardiomyopathy After Acute Kidney Injury by Signaling to Cardiomyocytes

Abstract: BACKGROUND: Acute kidney injury (AKI) is a short-term life-threatening condition that, if survived, can lead to renal insufficiency and development of chronic kidney disease. The pathogenesis of AKI and chronic kidney disease involves direct effects on the heart and the development of hypertrophy and cardiomyopathy. METHODS: We used mouse models of ischemia/reperfusion AKI and unilateral ureteral obstruction to investigate the role of IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 58 publications
(77 reference statements)
0
6
0
Order By: Relevance
“…Under normal conditions, IL33 is expressed in the cell nucleus and is secreted extracellularly in cases of infection, in ammation, tissue injury, and cell necrosis [5,26]. IL33 binds to its transmembrane receptor, ST2L, and the activated IL33/ST2 signal participates in critical pathophysiological processes including in ammation, brosis, and heart failure [27][28][29][30], suggesting the IL-33/ST2 pathway has broad clinical translational potential. The mechanism of increased intracellular IL33 expression remains unclear, but some studies suggest that Yap/Taz can directly regulate the IL33 promoter and promote its expression in cardiac broblasts [31].…”
Section: Discussionmentioning
confidence: 99%
“…Under normal conditions, IL33 is expressed in the cell nucleus and is secreted extracellularly in cases of infection, in ammation, tissue injury, and cell necrosis [5,26]. IL33 binds to its transmembrane receptor, ST2L, and the activated IL33/ST2 signal participates in critical pathophysiological processes including in ammation, brosis, and heart failure [27][28][29][30], suggesting the IL-33/ST2 pathway has broad clinical translational potential. The mechanism of increased intracellular IL33 expression remains unclear, but some studies suggest that Yap/Taz can directly regulate the IL33 promoter and promote its expression in cardiac broblasts [31].…”
Section: Discussionmentioning
confidence: 99%
“…Under normal circumstances, IL33 is expressed in the nucleus of the cell, and it is secreted to the outside of the cell in cases of infection, in ammation, tissue injury and cell necrosis [5,26]. IL33 binds to its transmembrane receptor, ST2L, and the activated IL33/ST2 signal is involved in important pathophysiological processes including in ammation, brosis, and heart failure [27][28][29][30], so it is considered that the IL-33/ST2 pathway has extensive clinical transformation value. The mechanism of increased intracellular IL33 expression remains unclear, but some studies have suggested that Yap/Taz can directly regulate the IL33 promoter and promote its expression in cardiac broblasts [31].…”
Section: Discussionmentioning
confidence: 99%
“…The biological role of IL33/ST2 signaling in cardiomyocytes is controversial. It has been reported that IL33 released after acute kidney injury can induce cardiomyocyte hypertrophy, showing a pathogenic effect [29], while in diabetic cardiomyopathy mice, IL33 administration can block autophagy and enhance cardiac diastolic function, thus having a protective effect [30]. In this study, we found that cardiomyocytes showed a signi cant SASP after administration of exogenous IL33, which was manifested as increased expression of SASP such as MCP1, IL1α and IL6, as well as increased number of SA-β-galactosidase active cells and the trend of cellular DNA damage, suggesting that the increase of IL33 has a damaging effect on cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies associate IL33 with worse cardiac outcomes, particularly post myocardial infarction [ 153 ]. Our research demonstrates that IL33 directly contributes to cardiac remodeling post AKI through the ST2 receptor on cardiomyocytes [ 154 ]. IL33 overexpression in mice led to a detrimental cardiac phenotype, whereas blocking IL33 during AKI protected the heart.…”
Section: Cardiorenal Butterfly Effectmentioning
confidence: 99%